Erratum: Acute and sub-acute toxicity of the crude extracts of the aerial parts of Daucus carota L. in laboratory rats - Ayodeji E. Ayeni; Ahmed Abubakar; Nuhu Aliyu; Lucia O. Uhomoibhi; Ibrahim Garba (AOSIS, 2021)
No abstract available.